2008
DOI: 10.1097/01.prs.0000298111.56163.3b
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Periosteal Brow Lift: Evaluation and Follow-Up of Eyebrow Height

Abstract: Subperiosteal endoscopic brow lift showed clinical and statistical effectiveness in correcting eyebrow ptosis, promoting also a spontaneous and progressive elevation of eyebrows, without enlarging the interbrow distance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…He found that the great majority of patients had an average of 2.5 mm higher eyebrows 5 years postoperatively compared to 1 year after surgery. Graf [35] also determined a progressive spontaneous increase in eyebrow height. Additionally, this elevation started in the medial portion of the brows.…”
Section: Pitfallsmentioning
confidence: 99%
“…He found that the great majority of patients had an average of 2.5 mm higher eyebrows 5 years postoperatively compared to 1 year after surgery. Graf [35] also determined a progressive spontaneous increase in eyebrow height. Additionally, this elevation started in the medial portion of the brows.…”
Section: Pitfallsmentioning
confidence: 99%
“…Romo et al 17 compared rabbits subjected to subperiosteal coronal rhytidectomy with skin resection and, using an absorbable screw fastener endoscopically and without skin resection, they Graf et al 7 analyzed a group of 72 patients who underwent endoscopic frontal rhytidectomy and found that in 38 patients analyzed between 3.5 and 8.5 months, there was a progressive and spontaneous elevation of the medial, central, and lateral areas in both eyebrows and saw the same effect in another 24 patients studied between 3.5 and 24 months. In this study, was found spontaneous stretch in the control group and the Sham group already present in the immediate postoperative period, which progressed by days 3 and 7, when it reached its peak.…”
Section: Discussionmentioning
confidence: 99%
“…69 In fact, some investigators found that eyebrow position continued to elevate during the first few postoperative months. 70,71 This was attributed to unopposed action of the frontalis muscle since the brow depressors were resected and the medial brow periosteum was released.…”
Section: Outcomes Of Endoscopic Forehead Midface Liftmentioning
confidence: 99%